The mevalonate pathway contributes to breast primary tumorigenesis and lung metastasis - Javier Conde; Isabel Fernández‐Pisonero; L. Francisco Lorenzo‐Martín; Rocío García‐Gómez; Berta Casar; Piero Crespo; Xosé R. Bustelo (Molecular Oncology)
The mevalonate pathway plays an important role in breast cancer and other tumor types. However, many issues remain obscure as yet regarding its mechanism of regulation and action. In the present study, we report that the expression of mevalonate pathway enzymes is mediated by the RHO guanosine nucleotide exchange factors VAV2 and VAV3 in a RAC1‐ and sterol regulatory element‐binding factor (SREBF)‐dependent manner in breast cancer cells. Furthermore, in vivo tumorigenesis experiments indicated that the two most upstream steps of this metabolic pathway [3‐hydroxy‐3‐methylglutaryl‐coenzyme A synthase 1 (HMGCS1) and 3‐hydroxy‐3‐methylglutaryl‐coenzyme A reductase (HMGCR)] are important for primary tumorigenesis, angiogenesis, and cell survival in breast cancer cells. HMGCR, but not HMGCS1, is also important for the extravasation and subsequent fitness of breast cancer cells in the lung parenchyma. Genome‐wide expression analyses revealed that HMGCR influences the expression of gene signatures linked to proliferation, metabolism, and immune responses. The HMGCR‐regulated gene signature predicts long‐term tumor recurrence but not metastasis in cohorts of nonsegregated and chemotherapy‐resistant breast cancer patients. These results reveal a hitherto unknown, VAV‐catalysis‐dependent mechanism involved in the regulation of the mevalonate pathway in breast cancer cells. They also identify specific mevalonate‐pathway‐dependent processes that contribute to the malignant features of breast cancer cells.